Pelabuhan-Pelabuhan Tradisional Di Pulau Ambon Dan Eksistensinya Bagi Masyarakat Maluku - Pusparani, Rina; Kilkoda, Muhammad Ramdhani; Pirasou, Alfia (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2021)
This study is titled Traditional Ports on Ambon Island and Their Existence for the People of Maluku. The research problems addressed in this study are as follows: How have the traditional ports of Ambon Island developed? And to what extent do these ports contribute to enhancing community mobility? The research method employed is qualitative with a descriptive approach. The purpose of this study is to apply maritime history research using historical research methods. By using an approach that considers development and social mobility, the study aims to produce a historical work that is not only descriptive-narrative but also analytical-structural. It is also hoped that this research will contribute to the enrichment of Maluku historiography, which still needs to be more sparse. Practically, this study will be useful, especially for government practitioners and policymakers, particularly in regional government agencies related to this issue. It will also be valuable for local government, especially in the Ambon Island and Lease Islands area, and for the people of Ambon City in general. Through a study of community development and change, this research can inform steps and policies to advance the community in the future without losing local wisdom.